The future challenges facing South African human resource management - Karl B. Hofmeyr; P. Johan Rall; Andrew J. Templer (South African Journal of Business Management, 1995)
In this article we set out to examine how human resource professionals view the challenges facing South African companies. The views of a representative sample of human resource professionals were obtained to find out, in particular, what changes they expect in human resources management (HRM) in the future and what priorities need to be set for successful human resources management in a changing environment. In terms of human resource management objectives, respondents indicate that currently the emphasis in their work is on efficiency, human resource development, and industrial relations. They believe the major objectives should, however, emphasize human resource development and facilitating change, with considerably less of their time being committed to industrial relations Issues. In terms of human resource activities, highest priority is given to managing organization change, affirmative action, and introducing participative management. Currently they are spending most of their time on industrial relations activities and training. Perhaps surprisingly, not much attention is being paid currently to the activities of cross-cultural management, and community upliftment and involvement. In the research we also investigate the balance of human resource responsibilities between HRM and line management. Activities which are perceived to be line management responsibilities are performance appraisal and employee communication. Those which should be a shared responsibility include employee development and affirmative action. Most respondents believe that the rate of progress with affirmative action is too slow. Perhaps predictably, human resource professionals see the most important challenge facing commerce and industry in the next five years to be the human resource challenge: in particular the need to improve productivity, affirmative action, training and development, and managing the demands of unions. The skills needed by human resource professionals to meet the challenges are sound 'business skills' as well as 'people skills'. They also need sound business knowledge and qualities of adaptability, empathy and sensitivity. In particular they need to be able to play a change agent role in their organizations.
Keywords: 650